Predictors of Complications and Mortality in Patients with Self-Expanding Metallic Stents for the Palliation of Malignant Colonic Obstruction - Sousa,Mafalda (2017)
Introduction: Self-expanding metallic stents (SEMS) for palliative purposes in malignant colonic obstruction are an alternative to surgery that has gained popularity over time. Methods: We performed a retrospective study of patients submitted to SEMS for palliation of obstructing malignant colorectal cancer from 2005 to 2015 to evaluate predictive clinical factors for complications and mortality. Results: Forty-five patients with high rates of technical and clinical success were included (97.8 and 95.6%, respectively), with complications occurring in 17.8% (8.9% perforations, 4.4% obstructions, and 4.4% migrations). The length of the stenosis was superior in patients with complications (p = 0.01); 11.1% of patients had a re-intervention (2.2% surgery and 8.9% placement of another SEMS). Relief of obstruction without intervention was maintained until death in 77.8% of patients and in 81.4% of patients who had immediate clinical success. The mortality rate was 37.2% at 30 days, 56.5% at 60 days, and 87.5% at 1 year. There were no predictors of survival identified, including age, sex, tumor stage, metastasis, or complications of the procedure. Discussion and Conclusions: In this study, SEMS placement was associated with a high rate of technical and clinical success and a low rate of complications, being an option to palliate patients with obstructive neoplasia. The length of the stenosis was associated with a greater risk of complications. The majority of stentrelated complications can be managed successfully without surgery.